State of the art research in: Clean Architecture and SOLID principles (Research, Society and Development, 2022)
The high demand for mobile services requires the adoption of an approach that meets the specific engineering requirements of mobile applications. Among these requirements are the creation of an architecture that separates responsibilities into layers and that adapts to change and corrections. It is in the architectural phase that the system takes shape by the developers. This form lies in the division of this system into components, in their organization and in the way they communicate with each other. In this sense, the present work proposed to elaborate a bibliometric review from the analysis of the scientific production on the approaches of Clean Architecture and SOLID, available in the database Periódico Capes, between the years 2012 and 2022. The results present a total of 27 scientific articles from the application of the search terms: clean architecture, mobile and software, of which four are aligned with the scope of the study, covering aspects related to the concept of clean architecture and the development of mobile applications using the SOLID approach , although of these, two are review articles, not considering the applicability of these concepts in the construction of new applications, thus demonstrating the lack of scientific production.